Evolving Customers Expectations of Japanese Restaurants in a Post-Covid Era: Indonesia Evidence - Anthony Cottan; John Purba; Anton Wachidin Widjaja; Rizaldi Parani (FIRM Journal of Management Studies, 2023)
AbstractThe popularity of Asian restaurants worldwide has been gaining momentum due to various attributes such as food trends, health concerns, and unique Asian flavors. Specifically in Indonesia, Japanese cuisine is booming due to, amongst other things, J-pop, tourism ties, and strong business relations. The 'pause' forced by Covid-19 seems to have created more attention to the healthier elements of Japanese cuisine, like naturally prepared Sushi, and subsequently, post-Covid era. The shifting customer expectations when choosing 'which' Japanese restaurant style is preferred should be understood in greater detail. This research investigates the Japanese restaurant industry in Indonesia through small focus group discussions. It utilizes a phenomenological qualitative technique to capture the lived experiences of consumers within the Indonesian market. While several studies exist to explore the evolving demands of consumers, few of them explore the topic from the view of consumers rather than restaurants or corporations.  The current study examines the topic from the perspectives of customers who currently and frequently visit Japanese restaurants in Indonesia. The study aims to understand better customers' intent to visit one Japanese restaurant versus another, alluding to what marketing approach the business needs to take to meet customer needs in a post-covid era.